IMPLEMENTASI NILAI-NILAI PANCASILA MELALUI PENDIDIKAN PANCASILA DI ERA MULTIKULTURALISME - Wati Solihat Sukmawati; Bahari, Bahari; Rheka Humanis Degawan; Nanang Zakaria; Marzuki, Marzuki (CV. ADIBA AISHA AMIRA, 2024)
The diversity of culture, ethnicity, religion, tribe, language and other aspects makes Indonesia a multicultural country that is recognized by other countries. There are positive and negative impacts of multicultural countries. Negative impacts include being able to cause differences of opinion, conflict, injustice, social integration and ethnocentrism. The aim of this research is to determine the implementation of Pancasila values through Pancasila education in the multicultural era. Writing scientific articles uses qualitative methods, using literature study collection techniques. The Pancasila values contained in it, such as cooperation, unity, tolerance, solidarity, mutual cooperation, are used as guidelines in social life. Thus, the values of Pancasila must already exist within the individual before acting in real life. So that multicultural life does not give rise to social conflicts that will destroy peace in the environment